2015
DOI: 10.1080/10911359.2015.1083502
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of African American female adolescent offenders 3, 4-Methylenedioxymethamphetamine (MDMA or “Ecstasy”) use and sexually transmitted infection morbidity

Abstract: The current study was designed to determine the extent to which self-reported ecstasy use in a population of juvenile adolescent detainees in a southern state is associated with high-risk health behaviors pertaining to sexually transmitted infection (STI) symptomology and past history of STI occurrence. Participants were 764 African American females extracted from an overall sample of 2,260 juvenile offenders housed at selected Youth Development Campuses in the state of Georgia. Significance tests were conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…Substance use has also been implicated in HIV/STI risk among young African Americans, including cigarette (Berg et al, 2012;Hill et al, 2014;Swartzendruber, Sales, Brown, DiClemente, & Rose, 2014;Waldrop-Valverde et al, 2013) cocaine (Ritchwood, DeCoster, Metzger, Bolland, & Danielson, 2016), opiate (Mulatu, Leonard, Godette, & Fulmore, 2008), ecstasy (J. M. Jackson et al, 2015;Stephens et al, 2016) and inhalant use (Berger, Khan, & Cleland, 2016) as well as general substance use problems (Woods-Jaeger, Jaeger, . However, alcohol and marijuana, the most commonly-used substances among African American adolescents and young adults (Miech, Johnston, O'Malley, Bachman, & Schulenberg, 2016), are the substances most often studied among this population, both showing consistent relationships with HIV/STI risk (e.g., Keen, Blanden, & Rehmani, 2016;Sales, Monahan, et al, 2014;Swartzendruber, Sales, Brown, DiClemente, & Rose, 2014;.…”
Section: Domain Specific Risk For Hiv/sti Among African American Yout...mentioning
confidence: 99%
“…Substance use has also been implicated in HIV/STI risk among young African Americans, including cigarette (Berg et al, 2012;Hill et al, 2014;Swartzendruber, Sales, Brown, DiClemente, & Rose, 2014;Waldrop-Valverde et al, 2013) cocaine (Ritchwood, DeCoster, Metzger, Bolland, & Danielson, 2016), opiate (Mulatu, Leonard, Godette, & Fulmore, 2008), ecstasy (J. M. Jackson et al, 2015;Stephens et al, 2016) and inhalant use (Berger, Khan, & Cleland, 2016) as well as general substance use problems (Woods-Jaeger, Jaeger, . However, alcohol and marijuana, the most commonly-used substances among African American adolescents and young adults (Miech, Johnston, O'Malley, Bachman, & Schulenberg, 2016), are the substances most often studied among this population, both showing consistent relationships with HIV/STI risk (e.g., Keen, Blanden, & Rehmani, 2016;Sales, Monahan, et al, 2014;Swartzendruber, Sales, Brown, DiClemente, & Rose, 2014;.…”
Section: Domain Specific Risk For Hiv/sti Among African American Yout...mentioning
confidence: 99%
“…This may be why some have suggested that such behavioral observations are consistent with maturational changes in brain observed from early to late adolescence specific to developmental brain chemistry [51]. Moreover, based on the aforementioned and since adolescence as a developmental period is marked by a greater probability to initiate drug use and with an increased risk to develop addiction and adulthood dependency [53], exploring cocaine use among adolescent with a history of problem behavior and interaction with the criminal justice system may enable the creation of more targeted interventions that focus on problem behavior, drug use and sexual risk taking [54].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, incarcerated individuals have a history of risky behavior in prison, such as sharing needles and unprotected sex, which favor the occurrence of this type of infection (7)(8) . Among the STIs most associated with this population are HIV, syphilis, genital herpes, viral hepatitis, gonorrhea, chlamydia, and HPV (9)(10)(11)(12)(13)(14)(15) .…”
Section: Introductionmentioning
confidence: 99%